Seroprevalence of SARS-CoV-2 among high-risk healthcare workers in a MERS-CoV endemic area - Fayhan Alroqi; Emad Masuadi; Lulwah Alabdan; Maysa Nogoud; Modhi Aljedaie; Ahmad S. Abu-Jaffal; Tlili Barhoumi; Abdulrahman Almasoud; Naif Khalaf Alharbi; Abdulrahman Alsaedi; Mohammad Khan; Yaseen M. Arabi; et al. (Elsevier, 2021)
Introduction: Healthcare workers (HCWs) in Saudi Arabia are a unique population who have had exposures to the Middle East Respiratory Syndrome coronavirus (MERS-CoV) and Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). It follows that HCWs from this country could have pre-existingMERS-CoV antibodies that may either protect from coronavirus disease 2019 (COVID-19) infection or cause false SARS-CoV-2 seropositive results. In this article, we report the seroprevalence of MERS-CoV and SARS-CoV-2 among high-risk healthcare workers in Riyadh city, Saudi Arabia. Methods: This is a cross-sectional study enrolling 420 high-risk HCWs who are physically in contact with COVID-19 patients in three tertiary hospitals in Riyadh city. The participants were recruited between the 1st of July to the end of December 2020. A 3 ml of the venous blood samples were collected and tested for the presence of IgG antibodies against the spike proteins of SARS-CoV-2 and MERS-CoV using enzyme-linked immunosorbent assay (ELISA). Results: The overall prevalence of SARS-CoV-2 in high-risk HCWs was 14.8% based on SARS-CoV-2 IgG testing while only 7.4% were positive by Polymerase Chain Reaction (PCR) for viral RNA. Most of the SARS-CoV-2 seropositive HCWs had symptoms and the most frequent symptoms were body aches, fever, cough, loss of smell and taste, and headache. The seroprevalence of MERS-CoV IgG was 1% (4 participants) and only one participant had dual seropositivity against MERS-CoV and SARS-CoV-2. Three MERS-CoV positive samples (75%) turned to be negative after using in-house ELISA and none of the MERS-CoV seropositive samples had detectable neutralization activity. Conclusion: Our SARS-CoV-2 seroprevalence results were higher than reported regional seroprevalence studies. This finding was expected and similar to other international findings that targeted high-risk HCWs. Our results provide evidence that the SARS-CoV-2- seropositivity in Saudi Arabia similar to other countries was due to exposure to SARS-CoV-2 rather than MERS-CoV antibody.